2013
DOI: 10.1002/2013jd020346
|View full text |Cite
|
Sign up to set email alerts
|

The potential of commercial microwave networks to monitor dense fog‐feasibility study

Abstract: [1] Here we show the potential for dense fog monitoring using existing measurements from wireless communication systems. Communication networks widely deploy commercial microwave links across the terrain at ground level. Operating at frequencies of tens of gigahertz, they are affected by fog and are, practically, an existing, sensor network, spatially distributed worldwide, which can provide crucial information about fog concentration and visibility. The goal of this paper is to show the feasibility for fog id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 56 publications
0
31
0
Order By: Relevance
“…In addition to hydrometeors, gaseous components (water vapor and molecular oxygen) and fog (David et al 2013) cause an offset with significant fluctuations of RSL depending on humidity and temperature (Ulaby et al 1981). Furthermore, the accumulation of water or water drops on the microwave link antennas can cause additional wet antenna attenuation that may lead to an overestimation of the attenuation caused by the precipitation along the link path (e.g., Overeem et al 2011;Schleiss et al 2013).…”
Section: B Processing Of the Microwave Link Measurementsmentioning
confidence: 99%
“…In addition to hydrometeors, gaseous components (water vapor and molecular oxygen) and fog (David et al 2013) cause an offset with significant fluctuations of RSL depending on humidity and temperature (Ulaby et al 1981). Furthermore, the accumulation of water or water drops on the microwave link antennas can cause additional wet antenna attenuation that may lead to an overestimation of the attenuation caused by the precipitation along the link path (e.g., Overeem et al 2011;Schleiss et al 2013).…”
Section: B Processing Of the Microwave Link Measurementsmentioning
confidence: 99%
“…Prior research has shown that the attenuation resulting from this phenomenon is of a magnitude around 0.5-1 dB . Figure 12a shows the attenuation caused by atmospheric gases for microwave frequencies up to 40 GHz and Figure 12b the attenuation caused by fog with different liquid water contents, including especially high values above 0.5 gr/m 3 (e.g., David et al, 2013;Gultepe et al, 2009;Niu et al, 2010) for the same range of frequencies.…”
Section: Results Analysismentioning
confidence: 99%
“…The effect of fog on microwave link attenuation has also been observed by e.g. Liebe et al (1989) and David et al (2013). 40 However, it is debatable whether the underlying cause is the wetting of the antennas or the attenuation by the fog droplets themselves.…”
Section: Dew and Fogmentioning
confidence: 97%
“…Several possible sources of error have been identified previously: the wet antenna effect and related dew formation on antennas (Minda & Nakamura, 2005;Leijnse, et 30 al., 2008), humidity and temperature (Minda & Nakamura, 2005), solid precipitation and spatial variability of precipitation (Berne & Uijlenhoet, 2007). Opportunities for simultaneous measurement of other environmental variables than rainfall have also been identified, such as evaporation (Leijnse, et al, 2007b), fog (Liebe, et al, 1989;David, et al, 2013), humidity (Chwala, et al, 2014) and hydrometeor type (Cherkassky, et al, 2014).…”
Section: Introductionmentioning
confidence: 99%